Impact of applying brief educational program on nurses knowledge, attitude, and practices toward pain management - Abozead, Shalabia El-Sayead; Al-Kalaldeh, Mahmoud; Al-Tarawneh, Omar (International Journal of Advanced Nursing Studies, 2015)
Background: The role of pain education is well established in improving knowledge and attitude towards the adherence to pain assessment and management.Methods: A brief pain education program was delivered to assess nurses' knowledge and attitude towards pain assessment and management. The "KASRP" scale was used at three phases; pre, post, and three months' follow-up phases. Subsequent eight months observation on using pain assessment sheets was also performed.Results: One hundred and four nurses were assessed at the beginning, followed by 92 at the immediate post-test, and 70 at the follow-up. Although nurses scored lowest in having knowledge and attitudes prior to the program, a significant improvement was evident after delivering pain education. In addition, nurses' competency in pain assessment was maintained over the three months of assessment. Younger nurses with shorter clinical experience were found more reactive to the program than older nurses.Conclusions: A brief nurse-driven pain education has improved nurses' knowledge and attitude towards pain management.